2014
DOI: 10.1136/jclinpath-2013-202075
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of gemcitabine enhanced by polyphenolics fromAronia melanocarpain pancreatic cancer cell line AsPC-1

Abstract: The implication of this study, using single cancer cell line, is that chemotherapy (at least with gemcitabine) might be usefully augmented with the use of micronutrients such as chokeberry extract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The lowest IC 50 values were observed forL2OB cells. Thani et al [45] reported that A. melanocarpa extract enhanced the cytotoxicity of gemcitamibe chemotherapy medication in the human pancreatic adenocarcinoma cell line ASPC-1.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest IC 50 values were observed forL2OB cells. Thani et al [45] reported that A. melanocarpa extract enhanced the cytotoxicity of gemcitamibe chemotherapy medication in the human pancreatic adenocarcinoma cell line ASPC-1.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the cytotoxic properties of either gemcitabine or doxorubicin, in presence or not of quercetin, were analyzed in AsPC-1 and HepG2 cell lines respectively, in order to evaluate any supra-additional effect. MDR1-inhibiting agents are known to be pharmacologically active in vitro in a concentration range from 1 to 15 μg /ml [35]. A range of 1-50 μM of the micronutrient quercetin was therefore chosen in this study, as minimally cytotoxic doses.…”
Section: Plos Onementioning
confidence: 99%
“…Studies with animal models and in vitro models show that chokeberry extracts and other products made from aronia fruit are effective in the prevention of carcinogenic occurrences due to their strong antioxidative action (Gąsiorowski and others ; Malik and others ; Zhao and others ; Lala and others ; Bermúdez‐Soto and others ,b; Shih and others ; Olas and others ; Balansky and others ; Kędzierska and others , ,b; Rugină and others ; Sharif and others ; Li and others ; Pratheeshkumar and others ; Thani and others ). The anticarcinogenic effect of aronia berry products is related to the antioxidative properties of polyphenolic compounds which protect healthy cells from oxidative damage induced by free radicals (Shih and others ), pro‐apoptotic action which enables the death of cells with carcinogenic changes (Rugină and others ; Sharif and others ), and the ability to arrest the cell cycle of tumor cells (Malik and others ; Zhao and others ; Bermúdez‐Soto and others ,b; Sharif and others ).…”
Section: Chokeberries and Their Products In The Prevention And Treatmmentioning
confidence: 99%
“…Chokeberry extract has pro‐apoptotic properties (Sharif and others ; Thani and others ). Cyanidin glycosides isolated from aronia fruit extract have been reported to induce an accumulation of peroxides in HeLa tumor cell culture which triggers apoptotic pathways in these cells (Rugină and others ; Sharif and others ).…”
Section: Chokeberries and Their Products In The Prevention And Treatmmentioning
confidence: 99%
See 1 more Smart Citation